The Influencing Factors and Countermeasures of Youth Political Participation - Revi, Asha L (Journal of Social Science and Humanities, 2024)
The youth have immense power to achieve their political goals. Youth have different perspectives towards politics which is determined their goals and objectives in the politics. By engaging in decision making, young people are learning about the political processes in society, but are also developing necessary skills, such as self - esteem, confidence, negotiation skills, a sense of autonomy etc. Thus participation is considered a tool for individual development of a young person as a citizen. Youth participation in politics encompasses a wide range of activities that allow individuals to form and express their views on the state of the world and how it is run, as well as to influence the decisions that directly affect their daily lives. This study discusses the factors that could influence political participation among youth. The purpose of this study is to examine the intuitional and exogenous factors of youth’s influencing political participation of youth’s. A total of 260 youths were participated in this survey, with a response rate of 100 % at the district level in Karnataka. Finding from multiple linear regression demonstrate that the influence of intuitional factors such as youth’s decision - making skills and political knowledge, youth’s technological sophistication and information literacy, political participation starts at the local, personality traits and attitude towards society, breaking a political nepotism, family background, voluntary activities and exogenous factors of youth’s such as contacting public officials, campaign activity, communal activities, role of students' unions/schools/colleges, political party programmes, financing and support, social environment, youth peer groups and associates, participation through voting have a substantial influence on political participation.